Plagiarism in Islamic Education, Online Learning and Student Self Efficay in the Time of Covid-19 - Prasetyo, Adirasa Hadi; Anwar, Khairul; Manurung, Alberth Supriyanto; Lestari, Novika; Jamilah, Jamilah (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
This article discusses plagiarism behavior among students and university students. Islamic education must be able to provide enlightenment and additional insight to students so that they stay away from plagiarism. This research is a literature review that is reviewed in depth and comprehensively. The research method is in the form of literature review by putting forward the relevant theory. The results of this literature review research are in the form of a relationship between Islamic education and the prevention of plagiarizing behavior in online learning and student self-efficacy.